ANALISIS KESULITAN PEMAHAMAN KONSEP MATEMATIS SISWA DALAM MENYELESAIKAN SOAL BENTUK ALJABAR DENGAN PROSEDUR NEWMAN - Nurikawai, Dian; Sagita, Laela; Setiyani, Setiyani (Universitas Papua, 2021)
Algebra is essential to learning mathematics and as a basis to support another mathematical concept. On the other hand, students have not fully mastered the concept of algebra which causes errors in solving problems. This qualitative research aims to describe students' misconceptions in solving algebraic questions based on the Newman method to understand mathematical concepts. The data were taken from six eighth-grade students at SMP N 1 Turi consisting of high, medium, and low abilities. The results of the analysis showed that the students did not make reading errors. Meanwhile, the misunderstanding of the question's students did not write down the information in the questions. It was because students were not used to writing what was known and asked in the questions. Students do not write down the strategies used, so that transformation errors are found. Errors in student process skills do not complete. The cause of this is an error in determining information on the questions and difficulties in solving them. The mistakes made by students in writing the final answer were not reporting the units and conclusions from the results of the solutions.